Kesetaraan Gender pada Pengkaderan Ulama di UIN Antasari - Nuril Huda; Difi Dahliana (Al-Ubudiyah: Jurnal Pendidikan dan Studi Islam, 2024)
The education of female clerics has been carried out, but the number of female clerics is still small compared to male clerics. In fact, the role of female scholars is just as needed as male scholars. This inequality of quantity makes the author interested in conducting research. Therefore, the research aims to analyze access, participation, control and benefits in the UIN Antasari Banjarmasin ulama regeneration program or the so-called PKU program. The design of this study is quantitative descriptive, where collection is carried out through questionnaires. Participants are cadres of ulama in the program. From the results of the study, there was no indication of gender injustice, all participants, both men and women, received the same access, participation, control and benefits while participating in the PKU program. Therefore, this program can be continued to produce male and female scholars who are gender responsive.